A New Way to Understand Healthy Sexual life:Traditional Medicine's Point of View - Elham Akhtari; Farnaz Sohrabvand (Tehran University of Medical Sciences, 2016)
Health is an essential issue in our lives.According toTraditional PersianMedicine (TPM), having healthy sexual relationship is an important aspect in preventivemedicine.This study was performed by searching through Canon of Medicine by Avicenna, Zakhireh Kharazmshahi andKamel al-Sanaeh inTPMaswell as themedical literature. Sexual function and its role in a healthy life style were considered.We looked for sexual life and its relationship with eating, types of drinking, bathing, sleeping habits and times and periods of a daymentioned in those references.InTPM, sexual life and intercourse are not only for pleasure.They are also important aspects of a healthy life style recommended to be performed with a certain frequency, in certain times, with a prologue and foreplay, and considering some limitations in drinking and eating.This study shows the essential role of a healthy sexual life according toTPMrecommendations.Regarding the effects of a healthy sexual style in generalwellbeing, it seems necessary to educate the public about related important issues in health clinics and primary care system.